Gut Microbiome Diversity and Composition in Captive Siberian Tigers (Panthera tigris altaica): The Influence of Diet, Health Status, and Captivity on Microbial Communities - You-Jeong Lee; Saebom Lee; Beoul Kim; Dongmi Kwak; Taehwan Kim; Min-Goo Seo (Microorganisms)
The gut microbiome is essential for the health of carnivorous mammals, including the endangered Siberian tiger (Panthera tigris altaica). However, limited research exists on the gut microbiome of captive Siberian tigers, especially regarding how diet and health status influence microbial diversity. This study addresses this gap by investigating the gut microbiome diversity and composition of six captive-born Siberian tigers housed at the Baekdudaegan National Arboretum in South Korea, using 16S rRNA gene sequencing. The study aimed to examine how diet and health status influence microbial communities, providing baseline data for managing captive tigers. Alpha diversity analysis revealed significant variation in microbial richness and evenness, with Tigers 2 and 6 exhibiting the highest microbial diversity and Tiger 3 the lowest, likely due to its surgical history and limited diet. Beta diversity analysis showed distinct microbial community structures influenced by diet and health. Taxonomic profiling identified Firmicutes and Bacteroidota as the dominant phyla, with Clostridium sensu stricto more prevalent in healthier tigers, while Escherichia-Shigella and Proteobacteria were abundant in tigers with lower diversity, suggesting dysbiosis. Comparisons with other tiger species confirm that diet, health, and captivity significantly shape the gut microbiome. These findings highlight the need for personalized health management in captive environments.